Synergistic acupuncture and neuromodulation for chronic insomnia: a structured narrative review with systematic search and future directions - Meng, Wang; Mingqiang, Wang; Junyang, Zhang; Bin, Peng; Qiong, Wu; Chao, Wang (Frontiers in Neurology, 2025)
Insomnia represents a significant global public health issue, affecting approximately 10% of adults with chronic symptoms and up to 20% with intermittent episodes. Closely associated with chronic diseases such as depression, anxiety, and cardiovascular conditions, insomnia markedly impairs patients’quality of life and imposes substantial economic burdens. Current treatments include pharmacological and non-pharmacological approaches. Pharmacotherapy primarily involves benzodiazepines, effective in short-term symptom relief but associated with long-term risks such as dependency, tolerance, and cognitive impairment. Recently introduced dual orexin receptor antagonists offer improved safety profiles but lack sufficient clinical evidence and remain costly. Melatonin and its receptor agonists have contentious efficacy, while antihistamines are discouraged for chronic use due to adverse effects. Herbal therapies have limited high-quality evidence to support routine clinical use. Among non-pharmacological treatments, cognitive behavioral therapy for insomnia (CBT-I) is recognized for clear efficacy, yet patient adherence and availability of trained specialists remain problematic. Exercise interventions, bright light therapy, and music therapy show preliminary positive effects; however, inconsistencies in intervention parameters and methodological quality necessitate further research. Recent advances highlight the potential of acupuncture and neuromodulation technologies, including transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), and vagus nerve stimulation (VNS). Acupuncture effectively improves sleep through modulation of autonomic nervous function, endocrine regulation, and remodeling of sleep-related neural circuits, demonstrating sustained benefits and high safety. Neuromodulation techniques offer rapid onset and precise targeting. Preliminary evidence indicates that combining acupuncture and neuromodulation techniques could synergistically enhance treatment efficacy, efficiency, and personalization. However, existing studies remain limited. Large-scale, multicenter randomized controlled trials are needed to clarify efficacy, safety, and to optimize clinical protocols for these integrative approaches. We conducted a structured narrative review with a systematic search (2010–2025), including 93 studies for qualitative synthesis; evidence certainty was summarized using four qualitative categories (High/Moderate/Low/Very low).